The Position of Digital Signatures in Notarial Practice According to The Principle of Tabelionis Officium Fideliter Exercebo - Supanji, Supanji; Adjie, Habib (LPPM Universitas Ekasakti Padang, 2024)
This research aims to investigate the role of digital signatures in notarization, focusing on their implementation and impact. Against the backdrop of developments in information technology, the use of digital signatures by Notaries is becoming increasingly relevant but also poses challenges in the process of making notarial deeds. The implementation of digital signatures can increase efficiency and security in making notarial deeds, but there are still obstacles related to certainty of time, place of deed making, and the need for more specific regulations related to cyber notary in Indonesia. The results of this study provide an in-depth understanding of the role of digital signatures in notaries and provide a basis for further development in integrating information technology in notarial practice.